Кровавый жемчуг: [роман] / Далия Трускиновская - Трускиновская Далия Мееровна (Ретродетектив, 2016)
Экземпляры: аб. (20241008) / Инвентарный номер: 65250 / Цена: / Сис.шифр: 84(2=411.2)6-4 / Авт.знак: Т 78 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-445.7